2002
DOI: 10.1177/174182670200900304
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Predict 12-month Prognosis in Elderly Patients with Acute Myocardial Infarction

Abstract: Background Several studies have associated depressive symptoms with an increased risk for cardiac events after the onset of acute myocardial infarction (AMI). The aim of the present study is to investigate the impact of the depressive symptoms on prognosis of the elderly patients with AMI.Method Depression was assessed in consecutive patients with AMI (n ¼ 1042; mean age 63 7 11 years) using the Zung Self-Rating Depression Scale (SDS). Patient with a score 40 was classified as having depressive symptoms. Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 46 publications
2
59
0
1
Order By: Relevance
“…40 The AHRQ EPC report identifi ed 6 independent studies meeting inclusion criteria that reported cardiac event rates among depressed patients. 50,[59][60][61][62][63] Studies were judged to be of moderate quality. One study 50 found that the association between cardiac events and depression disappeared with adjustment for fatigue symptoms, and 2 others found the same when adjusting for a measure of anxiety.…”
Section: Evidence Question 2: What Is the Prevalence Of Continued Depmentioning
confidence: 99%
“…40 The AHRQ EPC report identifi ed 6 independent studies meeting inclusion criteria that reported cardiac event rates among depressed patients. 50,[59][60][61][62][63] Studies were judged to be of moderate quality. One study 50 found that the association between cardiac events and depression disappeared with adjustment for fatigue symptoms, and 2 others found the same when adjusting for a measure of anxiety.…”
Section: Evidence Question 2: What Is the Prevalence Of Continued Depmentioning
confidence: 99%
“…Sixteen independent prospective studies were identified that had investigated whether or not depression predicted unscheduled care use in patients with either asthma, CHD, COPD or diabetes. 23,24,[28][29][30]55,57,68,[90][91][92][93][94][95][96][97] From the 16 studies, there were data for 8477 patients with LTCs (see Figure 3). Additional records identified through other sources (searching reference lists and citation searching of included papers) (n = 1914) Table 1 summarises the main characteristics of each of the included studies and is adapted from data in the published paper by Dickens et al 78 There were eight studies of COPD, 23,29,30,55,90,[94][95][96] five of CHD, 28,57,[91][92][93] two of asthma 24,68 and only one of diabetes.…”
Section: Evidence Synthesis (Phase 1)mentioning
confidence: 99%
“…Even low levels of depressive symptoms not typically associated with depressive disorder predict a 4-month mortality post-MI [10][11][12]. However, major depression following MI is a recognized predictor of disability, poor HRQoL [13][14][15] and mortality in the year post-MI.…”
Section: Introductionmentioning
confidence: 99%
“…According to BDI score range, patients were divided into 4 groups: minimal (0-13), mild (14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28) and severe depression (29-63) groups. …”
Section: Beck Depression Inventory (Bdi)mentioning
confidence: 99%